Efficacy of fluoroscopy-guided triple shoulder injection for older patients with nonspecific shoulder pain - (:unkn) unknown (SPRINGER, 2019)
Key Summary PointsAimThe study was to evaluate the effects of fluoroscopy-guided triple shoulder injection (i.e. injection into glenohumeral joint, subacromial space, and acromioclavicular joint) on pain and function in older patients with nonspecific shoulder pain.FindingsA significant improvement was detected in pain, and function at 3 and 12 weeks after injection compared with baseline.MessageFluoroscopy-guided triple shoulder injection offers a therapeutic option for older patients with nonspecific shoulder pain. AbstractPurposeNonspecific shoulder pain is a common complaint in older adults that impairs physical function by restricting the range of joint movement, and causing severe pain. The study evaluated the effects of fluoroscopy-guided triple shoulder injection [i.e., injection into glenohumeral (GH) joint, subacromial (SA) space, and acromioclavicular (AC) joint] on pain, function, and range of motion in older patients with nonspecific shoulder pain.MethodsA total of 43 patients who were aged 65years and older and diagnosed with nonspecific shoulder pain were included in this prospective, non-randomized clinical trial; 65.1% of the patients were female and mean age was 70.25.0. Under fluoroscopic guidance, a mixture of methylprednisolone and bupivacaine was injected into the GH joint, SA space and AC joint. Patients were evaluated as per the Numeric Rating Scale for Pain (NRS-Pain), the Shoulder Pain and Disability Index (SPADI), and the active range of motion (AROM) at baseline, and again at 3 and 12weeks after the injection.ResultsA statistically significant improvement was detected in NRS-Pain, SPADI, and AROM at 3 and 12weeks after injection compared with baseline. The change in SPADI score from baseline was higher than the minimal detectable change in 67.4% of patients at 12weeks. The SPADI score at baseline was positively correlated with the post-injection SPADI score at 3 and 12weeks.Conclusions In older patients with nonspecific shoulder pain, fluoroscopy-guided triple shoulder injection provides significant improvements in pain and physical function with low complication rates during the 12-week follow-up.
Keywords: Aged; Shoulder pain; Injections; Fluoroscopy; Magnetic resonance imaging; SUPRASCAPULAR NERVE BLOCK; CORTICOSTEROID INJECTIONS; ABNORMALITIES; POPULATION; PREVALENCE; ULTRASOUND; MANAGEMENT